2016
DOI: 10.1007/s13197-016-2244-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high hydrostatic pressure on rheological and thermophysical properties of murtilla (Ugni molinae Turcz) berries

Abstract: Effects of high hydrostatic pressure (HHP) on rheological and thermophysical properties of murtilla berries were evaluated after pressure treatments for 5 min between 100 and 500 MPa. Differential scanning calorimetry was employed to measure specific heat capacity. HHP caused a significant decrease in specific heat and density, while thermal diffusivity did not changed significantly. Thermal conductivity showed a slight increase upon HHP treatment. Apparent viscosity increased significantly above 200 MPa HHP t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…showed that high‐pressure processing at 100 or 200 MPa could increase the viscosity of mango puree. Furthermore, the treatment of murtilla puree with a high pressure of 200 MPa or greater for 5 min significantly increased the viscosity of the puree, which was most significant with 500 MPa treatment 20 . From the aforementioned literature, the applied pressure positively correlated with increase in viscosity, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…showed that high‐pressure processing at 100 or 200 MPa could increase the viscosity of mango puree. Furthermore, the treatment of murtilla puree with a high pressure of 200 MPa or greater for 5 min significantly increased the viscosity of the puree, which was most significant with 500 MPa treatment 20 . From the aforementioned literature, the applied pressure positively correlated with increase in viscosity, which is consistent with the results of this study.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the treatment of murtilla puree with a high pressure of 200 MPa or greater for 5 min significantly increased the viscosity of the puree, which was most significant with 500 MPa treatment. 20 From the aforementioned literature, the applied pressure positively correlated with increase in viscosity, which is consistent with the results of this study. As for the delayed glucose response, the release of glucose in the puree was delayed as the applied pressure increased.…”
Section: Glycaemic Indexsupporting
confidence: 92%
See 1 more Smart Citation
“…However, ohmic heating did not cause any change in the flow behavior of mulberry puree since both control and ohmic-treated products followed the same rheological model. Studies on various processing methods for fruit juice and puree, such as ultrasound [Rojas et al, 2016], vacuum evaporation [Sabanci & Icier, 2020], and high hydrostatic pressure [Lemus-Mondaca et al, 2016], have reported that processing methods did not cause an overall change in the flow behavior. However, distinct changes were observed in the rheological characteristics, such as consistency coefficient, flow behavior index, and yield stress.…”
Section: Results and Discussion The Electrical Conductivity Of Mulberry Pureementioning
confidence: 99%
“…Many authors [Bozkurt & Icier, 2009;de Castilhos et al, 2018;Deshmukh et al, 2015] have indicated that rheological properties can be used as a basis for operating design, processing optimization, and quality evaluation. Rheological characteristics of fruit puree are affected by temperature, concentration, ripening stage of fruit, product formulation, and processing method [Gomathy et al, 2015;Lemus-Mondaca et al, 2016]. The use of heat treatment combined with the continual stirring and pumping may result in undesirable effects on the product such as structural breakdown, which in turn can affect sensory quality and consistency coefficient of the product [Gomathy et al, 2015].…”
Section: Introductionmentioning
confidence: 99%